Análise dos contratos de agência ou representação comercial e de distribuilçao ou revenda em face das disposições do código civil, lei N. 10.406 DE 10/1/02 - Gago, Viviane Ribeiro (2006)
This dissertation considers the analysis of agency or commercial representation agreements and distribution or resale agreements under the provisions of the Civil Code, Law nr. 10.406, of 10th Jan, 2002. It includes aspects related to contractual rights, business activities, circulation of riches, economic scope, involving all contractual types above-mentioned. There is a brief research on the subject regarding legislation of other countries. In addition, there are comments on the concepts of these agreements. Judiciary jurisdiction and jurisprudence on the matter are also object of analysis of this study